Профілактика ротації торичних інтраокулярних лінз після факоемульсифікації катаракти на очах з рогівковим астигматизмом з використанням стандартного капсульного кільця - Завгородня, Наталія Григорівна; Новікова, Валерія Юріївна; Цибульська, Таміла Євгенівна; Zavgorodnya, Nataliia; Novikova, Valeriia; Tsybulska, Tamila (Warsaw : RS Global Sp. z O.O., 2021)
We have developed a method of preventing TIOL rotation by using a standard capsule ring. We examined 46 patients (59 eyes) who underwent phacoemulsification and implanted TIOL. Rotation of TIOL 6 months after surgery in the control group with 22 eyes (70.9%), in the main group - with 12 eyes (42.85%). In the main group in all cases, the deviation of the TIOL axis did not exceed 6 degrees. The proposed method of prevention of rotation of TIOL allows to increase the efficiency of phacoemulsification of cataracts.
Prevention of Toric Intraocular Lens Rotation After Cataract Phacoemulsification in the Eyes with Corneal Astigmatism Using a Standard Capsule Ring
Завгородня Н. Г. - https://orcid.org/0000-0002-5678-4196; Новікова В. Ю. - https://orcid.org/0000-0002-6370-6348; Цибульська Т. Є. - https://orcid.org/0000-0002-1745-7002
Keywords: cataract; corneal astigmatism; cataract phacoemulsification; toric IOL; astigmatic correction